Manifesto of the Communist Party 170 Years After The First Edition: Introduction to the Thematic Issue of Sociološki pregled / Sociological review - Vratuša, Vera A. (Sociološki pregled, 2018)
One century and seventy years that passed since the frst publishing of the Manifesto of the Communist Party (Marx, Engels, 1848), present a good reason to invite the interested authors to reﬂect on the actuality of main theses of Marx and Engels who summarized them already in this programmatic work while they were still in their twenties, elaborating these theses further in later works, closely related to ups and down of the proletarian class struggle. In the following paragraphs we will review the main theses that are still relevant for understanding the contemporary historical processes and for orienting the action of anti systemic social movements.
Keywords: social revolution; small bourgeoisie; proletariat; bourgeoisie; Manifesto of the Communist Party